2006
DOI: 10.1111/j.1365-2494.2006.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defoliation management, based on leaf stage, on perennial ryegrass (Lolium perenne L.), prairie grass (Bromus willdenowii Kunth.) and cocksfoot (Dactylis glomerata L.) under dryland conditions. 1. Regrowth, tillering and water‐soluble carbohydrate concentration

Abstract: Effect of defoliation management, based on leaf stage, on perennial ryegrass (Lolium perenne L.), prairie grass (Bromus willdenowii Kunth.) and cocksfoot (Dactylis glomerata L.) under dryland conditions. 1. Regrowth, tillering and water-soluble carbohydrate concentration Abstract A field study was undertaken between April 2003 and May 2004 in southern Tasmania, Australia to quantify and compare changes in herbage productivity and water-soluble carbohydrate (WSC) concentration of perennial ryegrass (Lolium pere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
59
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 36 publications
(56 reference statements)
13
59
0
8
Order By: Relevance
“…This effect of defoliation frequency on DM production was similar for all the tested entries. These results are in agreement with previous grazing and defoliation studies (Turner et al 2006b;Pontes et al 2007), which reported D. glomerata stand deterioration over time due to frequent defoliation.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This effect of defoliation frequency on DM production was similar for all the tested entries. These results are in agreement with previous grazing and defoliation studies (Turner et al 2006b;Pontes et al 2007), which reported D. glomerata stand deterioration over time due to frequent defoliation.…”
Section: Discussionsupporting
confidence: 83%
“…This could explain the reduced DM production under frequent defoliation during the second year. increased DM production under infrequent defoliation during the second year could be attributed to greater WSC assimilation and therefore leaf and tiller DM accumulation during the subsequent recovery period (Rawnsley et al 2002;Turner et al 2006b). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated defoliation before the two-leaf stage depleted water soluble carbohydrate reserves and delayed regrowth of leaves and roots, while defoliation after the three-leaf stage resulted in the loss of older leaves through death and decay [94]. Leaf-stage grazing rules based on similar principles have been developed for cocksfoot (Dactylis glomerata L.) [95,96], prairie grass (Bromus willdenowii Kunth.) [97,98], and tall fescue [31].…”
Section: Grazing Management Of Water-stressed Pasturesmentioning
confidence: 99%
“…Unfortunately the grazing management requirements to optimise DM yield, persistence and nutritive value of many grasses, legumes and forbs (Sanderson et al 2003, Labreveux et al 2006, Turner et al 2006, Lee et al 2012 do not align with each other or align with perennial ryegrass and white clover. However, there are examples of some species combinations with aligning grazing management which could be components of diverse pastures (e.g.…”
Section: Management Of Simple and Diverse Pasturesmentioning
confidence: 99%